2008
DOI: 10.1017/s0025315408000337
|View full text |Cite
|
Sign up to set email alerts
|

Gametogenic cycle of the smooth clam Callista chione on the south-western coast of Portugal

Abstract: The gametogenic cycle of the smooth clam Callista chione off the Arrábida region was studied throughout a 17-month period (from January 2004 to May 2005) using standard histological techniques, mean oocyte diameters and a condition index. This species showed a synchronism between sexes both in terms of gametogenic development and spawning. The results indicated that sex-ratio was not significantly different from parity. In January 2004, the gametogenic cycle had already begun and ended in late October 2004. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 21 publications
4
26
2
Order By: Relevance
“…Using these VBG equations and the size at first maturation previously estimated for this Callista chione population (50.81 mm SL; Moura et al 2008), we estimated the respective age at first maturity. According to these calculations, the smooth clam off Arrábida reaches sexual maturation at between 4.25 (surface growth rings) and 4.44 yr of age (internal growth bands).…”
Section: Resultsmentioning
confidence: 99%
“…Using these VBG equations and the size at first maturation previously estimated for this Callista chione population (50.81 mm SL; Moura et al 2008), we estimated the respective age at first maturity. According to these calculations, the smooth clam off Arrábida reaches sexual maturation at between 4.25 (surface growth rings) and 4.44 yr of age (internal growth bands).…”
Section: Resultsmentioning
confidence: 99%
“…in July, January and March, indicating several reproductive events within a year. In the coastal waters of southwest Portugal, C. chione showed three spawning peaks between January and October (Moura et al 2008). The occurrence of several reproductive peaks throughout the breeding season is likely to be an adaptation that favors, by risk spreading, successful recruitment rather than relying on the survival of one large cohort per year.…”
Section: Discussionmentioning
confidence: 97%
“…Moura et al (2008) noted that changes in body condition index in C. chione followed the gametogenic cycle; flesh weight increased prior to spawning and decreased during spawning. Previous studies of gonad development in C. chione have indicated that this bivalve is capable of year-round reproduction, having a prolonged reproductive cycle with simultaneous presence of gametes in various stages of maturation (Metaxatos 2004;Moura et al 2008). In our study, three peaks in condition index were noted, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations